Output growth and fluctuation: the role of financial openness - Alexander Popov (European Central Bank (ECB), 2011)
I analyze output growth, volatility, and skewness as the joint outcomes of financial openness. Using an industry panel of 53 countries over 45 years, I find that financial openness increases simultaneously mean growth and the negative skewness of the growth process. The increase in output skewness appears to come from a more negatively skewed distribution of investment, TFP, and new business creation. The growth benefits of financial liberalization are augmented, and its costs associated with higher probability of rare large contractions are mitigated by deep credit markets and by strong institutions. The main result of the paper holds in aggregated data.
Keywords: E32; F30; F36; F43; G15; 330; Development; Financial openness; Growth; skewness; Volatility